2014
DOI: 10.1080/19393210.2014.945195
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic food colours in saffron solutions, saffron rice and saffron chicken from restaurants in Tehran, Iran

Abstract: Saffron solutions, saffron rice and saffron chicken samples were considered for synthetic colours as additives, which are forbidden according to Iranian national standards. Samples were taken from restaurants of three locations and analysed by high-performance liquid chromatography. Of the total 573 samples, 52% were positive for at least one colour. The most prevalent colours were Tartrazine, Quinoline Yellow and Sunset Yellow, with 44%, 9.1% and 8.4% of the samples testing positive for these colours, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this systematic review of literature, 11 of the fulltext articles reported that misuse of food additives in the food market endangers public health [57][58][59][60][61][62][63][64][65][66][67]. Food additive is any substance not normally consumed as a food by itself; not normally used as a typical ingredient of the food (whether or not it has nutritive value); and added intentionally to food for a technological purpose in the production process for the purpose of maintaining This study investigated food safety and public health issues in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review of literature, 11 of the fulltext articles reported that misuse of food additives in the food market endangers public health [57][58][59][60][61][62][63][64][65][66][67]. Food additive is any substance not normally consumed as a food by itself; not normally used as a typical ingredient of the food (whether or not it has nutritive value); and added intentionally to food for a technological purpose in the production process for the purpose of maintaining This study investigated food safety and public health issues in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Moradi-Khatoonabadi et.al determined synthetic dyes from saffron chicken, saffron solutions, and saffron rice samples obtain from restaurants and found that 52% of samples were positive for at least one synthetic dye; and the prevalent dyes were Tartrazine (44%), Quinoline Yellow (9.1%), and Sunset Yellow (8.4%). [26] In a survey conducted in Arak city of Iran, synthetic illegal dyes such as Sunset Yellow, Tartrazine, Quinoline Yellow, Azorubine, and Allura Red were detected in 56 out of 70 samples (80%) of cookies, ice cream, and saffron aqueous solutions obtained from confectionaries and restaurants. [27] In Hong Kong, the occurrence of synthetic colors was determined in snacks and found that Tartrazine (27.5%) and Sunset Yellow (24.0%) were the most commonly used synthetic colorants.…”
Section: Resultsmentioning
confidence: 99%
“…The dietary exposures to B1, B2, and B6 vitamins were calculated using the Monte Carlo approach. The EDI (mg/kg day) is applied to quantify the oral exposure dosage for vitamins and estimated by the following Equation (Jahanbakhsh et al., 2019; Rezaei et al., 2019):EDI=C×ED×EF×IRBW×ATwhere EDI is the estimated daily intake (mg/kg day), C is vitamin concentration (mg/kg), IR is ingestion rate (110 g/day), ED is exposure duration (70 years), EF is exposure frequency (365 days/year), BW is reference body mass (the mean weight of children and adults is between 15 and 70 kg, respectively), and AT is the mean time (for both children and adults, it is 25,550 days, respectively) (Jahanbakhsh et al., 2019; Madani‐Tonekaboni et al., 2019; Moradi‐Khatoonabadi et al., 2015; Nikooyeh et al., 2016; Saha & Zaman, 2013).…”
Section: Methodsmentioning
confidence: 99%